Medical students’ interest in research: changing trends during university training - Sanabria-de la Torre, Raquel; Quiñones-Vico, María I.; Ubago-Rodríguez, Ana; Buendía-Eisman, Agustín; Montero-Vílchez, Trinidad; Arias-Santiago, Salvador (Frontiers in Medicine, 2023)
Introduction Research is an important aspect of medical training and plays a vital role in the advancement of evidence-based medicine. However, little is known about medical students’ attitudes towards research. So, the aim of this study was to assess the opinion of medical students on scientific research. Methods A cross-sectional study was designed that included students from the Faculty of Medicine of the University of Granada (UGR), Granada, Spain. A survey was distributed to assess their interest about research during undergraduate studies (1) and following graduation (2), participation in research activities (3), barriers towards research (4), expectation values and self-perceived skills (5). The opinions of students who had not taken clinical subjects (2nd year students) and students who had taken clinical subjects (4th and 6th year students) were compared. Results 91 students were included in the study (32 were 2nd year students and 59 were 4th and 6th year students). More 4th and 6th year students showed no interest in research (50.4% vs. 28.1%, p = 0.042) or in pursuing a doctoral thesis (75% vs. 50.9%, p = 0.079) than 2nd year students. In addition, more 4th and 6th year students felt that they did not have sufficient skills to engage in scientific research (52.4% vs. 18.9%, p = 0.002). Likewise a greater number of 4th and 6th year students considered that the professors did not encourage scientific research activities (74.6% vs. 40.6%, p = 0.002). Generally, students do not participate in scientific dissemination events. The main barriers to research identified were lack of funding and lack of awareness of opportunities. Conclusion Interest in research among medical students seems to decrease as the academic years progress. More research promotion could be implemented during the years of university studies.